The Degree of Teachers’ Use of The Skills of the Cort in Teaching Biology "A field study in basic education schools in the city of Lattakia" - نصور رغداء; حمدان ميساء; كادونة عائشة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims to identify the degree of use of teachers in the Second cycle of basic education for skills of the CoRT in the teaching of biology, as well as knowing the differences they have in using these skills, according to the educational qualification variable, and the number of years of experience teaching, where the sample consisted search of (303) teachers from teachers of the second cycle of basic education has been chosen way Statistics from the second cycle of basic education schools in the city of lattakia, and applied them to identify the use of skills of the CoRT in the teaching of biology (the researcher) after verifying the validity and reliability. The results indicated the following: The existence of a weak degree by the teachers of the second cycle of basic education in their use of the skills of the CoRT in teaching biology. There were statistically significant differences between mean scores of teachers in the second cycle of basic education to identify the use of Skills of the CoRT in the teaching of biology, according to the variable of qualification for the benefit of teachers with graduate qualifications (Diploma / Graduate). There were statistically significant differences between mean scores of teachers in the second cycle of basic education to identify the use of skills of the CoRT in the teaching of biology, according to a variable number of years of experience for the benefit of teachers with years of experience (5 years and more).